Current Epidemiology and Trends in Meningococcal Disease—United States, 1996–2015. (8th November 2017) - MacNeil, Jessica R; Blain, Amy E; Wang, Xin; Cohn, Amanda C
Abstract : This paper describes the current epidemiology and trends in meningococcal disease in the United States. Incidence has declined dramatically among all age groups and predominant serogroups. Reductions in incidence among adolescents suggest an impact of vaccination in this age group. Abstract: Background: In 2005, meningococcal conjugate vaccine (MenACWY) was recommended for routine use among adolescents aged 11–18 years. This report describes the epidemiologic features of meningococcal disease and trends in meningococcal disease incidence following MenACWY introduction in the United States. Methods: Incidence rates and case-fatality ratios by age group and serogroup during 2006–2015 were calculated using data from the National Notifiable Diseases Surveillance System (NNDSS); changes in incidence during this time were evaluated. Additionally, 20-year trends (1996–2015) in age- and race-standardized incidence were examined using data from Active Bacterial Core surveillance (ABCs). Results: During the years 2006–2015, 7924 cases of meningococcal disease were reported to NNDSS, resulting in an average annual incidence of 0.26 cases per 100000 population; 14.9% of cases were fatal. Among cases with serogroup information, 2290 (35.8%) were serogroup B, 1827 (28.5%) were serogroup Y, 1457 (22.8%) were serogroup C, 436 (6.8%) were serogroup W, and 392 (6.1%) were other serogroups. The incidence of serogroups A, C, W, and Y combined declined 76% among persons aged 11–20 years from 2006–2010 to 2011–2015 ( P < .0001). From 1996 through 2015, the incidence of meningococcal disease declined among all age groups and predominant serogroups. Conclusions: Declines in meningococcal disease incidence in the United States have been observed among all age groups and predominant serogroups (B, C, and Y). Reductions in the incidence of meningococcal disease due to serogroups A, C, W, and Y among adolescents suggest an impact of the MenACWY vaccine program in this age group.